2013
DOI: 10.1007/s11033-013-2710-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Wnt-Frizzled signaling in cardiovascular diseases

Abstract: Wnts are secreted glycoproteins implicated in biological processes ranging from embryonic cardiac development to uncontrolled cell proliferation in diseased conditions. Cardiovascular disease is a major cause of morbidity and mortality worldwide. Phenotypic modulation of vascular smooth muscle cells, migration and proliferation in intimal layer and increased extracellular matrix production are some of the known hallmarks of cardiovascular pathologies. Heterogeneity associated with the binding of Wnts to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…Defective Wnt signaling can result in various cardiac and vascular abnormalities. Moreover, in other studies, it was indicated that Wnt signaling is involved in cardiovascular diseases coupled with ion channels and cardiac hypertrophy [35,36]. In the present study, b-catenin expression was detected in human infarct hearts and in diseased animal model hearts.…”
Section: Discussionsupporting
confidence: 60%
“…Defective Wnt signaling can result in various cardiac and vascular abnormalities. Moreover, in other studies, it was indicated that Wnt signaling is involved in cardiovascular diseases coupled with ion channels and cardiac hypertrophy [35,36]. In the present study, b-catenin expression was detected in human infarct hearts and in diseased animal model hearts.…”
Section: Discussionsupporting
confidence: 60%
“…Induction of these pathways is also verified in ISR versus non-ISR tissue. Substantial evidence indicates that the Wnt, HH, BMP and Notch pathways play a role in the physiological differentiation and homeostasis of epithelial cells, and that the alterations of these pathways contributes to the pathophysiology of skeletal and cardiovascular diseases and tumorigenesis [17,18,19,20,21,22,23,24]. These pathways also appear to have cross-talk among them [25,26,27,28,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…This increased expression of Wnt1 appears to be protective since loss of Wnt1 translates into progressive spinal cord injury [ 198 ], impaired neurogenesis [ 199 ], and apoptosis [ 156 , 193 , 200 ]. Wnt1 signaling pathways can prevent cellular injury during experimental diabetes [ 28 , 201 ], ischemic brain injury [ 197 , 202 ], dopaminergic neuronal cell injury [ 179 , 189 , 195 , 203 ], toxic environments for microglia and other inflammatory cells [ 69 , 104 , 191 , 193 ], and neuronal synaptic dysfunction [ 204 ]. Wnt signaling can afford cellular protection against apoptotic cell death through the inactivation of FoxO proteins.…”
Section: Forkhead Transcription Factors Oxidative Stress Apoptosmentioning
confidence: 99%